JURIDICAL ANALYSIS OF THE STATUS OF INHERITANCE OF CHILDREN OUTSIDE OF MARRIAGE ACCORDING TO CIVIL LAW - Rohmah, Mayza H; Harianti, Isnin; Riawanto, Riawanto (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
This preparation is the result of a written audit to answer the question: (1) What is the status and position of inheritance rights for children present only from one parent as referred to by Civil Law? (2) How is the distribution of inheritance to children outside of marriage as referred to in civil law? The research method used is a kind of juridical normalization research, particularly legal examination, so it centers on positive legal invemtaris, legitimate standards and teachings, legal discovery, systematic law, synchronization rate, legal correlation, and legal history. The author also uses case approach techniques, these strategies are used to consider legal standards or decisions completed in lawful practice. Data sources are obtained from:(1) primary materials; and (2) secondary materials. Judging from the arrangement of this theory, it can be obtained the following results: (1) based on Law No. 16 of 2019 article 43 paragraph 1, a child without the presence of a father who is not considered consequently has social equality from his mother and his mother's family; (2) Based on article 280 of the Criminal Code there are 2 different ways for the recognition of a child without the presence of a father, namely intentional confession and coercive confession; (3) In article 863 of the Criminal Code tends to explain that children with one parent only who is present with the heirs of group I get 1/3 of the legal child, if with group II or III the heir gets 1/2 inheritance, if with bunch group IV get 3/4 inheritance, and with heirs who do not leave a valid heir, The outer child of marriage acquires all the inheritance